(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the value of transperineal ultrasound (TPUS) in assessing pelvic organ prolapse (POP) in women, using dynamic pelvic floor magnetic resonance imaging (MRI) as a reference. Methods: A cross-sectional study was conducted on 10 female patients with suspected or confirmed Pelvic Organ Prolapse (POP) at Hanoi Medical University Hospital (August 2025–March 2026). Assessed parameters included bladder, uterine, and rectal descent, as well as levator hiatus measurements (anteroposterior diameter, transverse diameter, and area) at rest and during dynamic maneuvers. Correlation and agreement between transperineal ultrasound and MRI were evaluated using Pearson correlation, intraclass correlation coefficient (ICC), and Bland–Altman analysis. Results: At rest, strong correlations were observed between transperineal ultrasound and MRI (r = 0.94–0.98; p < 0.001), with small mean differences and high ICC values (0.94–0.96). Under dynamic conditions, correlations decreased but remained statistically significant (r = 0.66–0.90; p < 0.05), with lower ICC values (0.49–0.84). Negative mean bias at dynamic phases indicated that transperineal ultrasound tended to underestimate the degree of prolapse compared to MRI. Conclusion: Transperineal ultrasound demonstrates good correlation and agreement with MRI in the assessment of POP, particularly at rest. It may serve as a useful initial imaging modality in clinical practice; however, further studies with larger sample sizes are required to validate these findings.